2018
DOI: 10.1017/s1463423618000622
|View full text |Cite
|
Sign up to set email alerts
|

Medical waste management improvement in community health centers: an interventional study in Iran

Abstract: Aim To improve the medical waste management (MWM) standards in Tabriz community health centers (CHCs) through clinical audit process. Background Management of medical waste is not only a legally necessity but also a social responsibility in health systems. Owing to the potential risks for human health and environmental impacts, MWM is a global concern. Methods This was an interventional research designed using clinical audit cycle that was implemented in Tabriz CHCs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…Some of the issues identified in PSWRs were common topics such as medical waste management and infection control which required a systematic teamwork. 20 These issues were shared between the various departments of hospital. This provided an opportunity for department employees to learn each other's experiences and strategies in resolving the safety problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the issues identified in PSWRs were common topics such as medical waste management and infection control which required a systematic teamwork. 20 These issues were shared between the various departments of hospital. This provided an opportunity for department employees to learn each other's experiences and strategies in resolving the safety problems.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the issues identified in PSWRs were common topics such as medical waste management and infection control which required a systematic teamwork . These issues were shared between the various departments of hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The survey further revealed that the average number of stakeholders are aware of the manual and guidelines provided by WHO and State Pollution Control Board, but very few could produce the actual document citing guidelines and preventive measures. Hence, it is the responsibility of the concerned HCE to provide this document to everyone involved in the process of generation and handling of HCSW (Tabrizi et al , 2019). The survey has shown that a significant number of stakeholders are not even aware of the team responsible for HCSWM in their HCEs.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses and technicians are important stakeholders, as they are involved in the process of generating most of the HCSWs. It was observed that most of the stakeholders, except doctors, are not aware of the waste handling practices related to their department as well as the complete HCSWM process, which has been noticed as another drawback of the current HCSWM system (Doylo et al, 2019;Tabrizi et al, 2019;Gupta et al, 2016). Similar results are found in a survey conducted in one of the largest hospitals (2,873 bedded hospitals) in New Delhi, India, which has shown that MEQ 32,3 doctors are mostly aware of the waste handling practices, but the housekeeping staff is unaware of most of the guidelines (Hosny et al, 2018).…”
Section: Awareness Among Various Stakeholdersmentioning
confidence: 99%
“…However, because the PHC system covers a broader population as the first level of health services delivery, greater attention must be paid to MWM in PHCs. 6,7 We suggest that researchers conduct intervention studies on MWM in PHCs using quality improvement methods such as Audit, 8 which may lead to improvements in adherence to MWM standards in Azerbaijan, Iran, and elsewhere.…”
mentioning
confidence: 99%